Evaluation of the dynamic response for scaled models of shaped concrete floor slabs. Issue 2 (June 2023) - Broyles, Jonathan M; Shepherd, Micah R; Brown, Nathan C
The dynamic response of building structures is an essential design consideration in building acoustics. However, building design is increasingly driven by sustainability goals. Floors can be optimized to reduce material consumption and corresponding carbon emissions, yet geometric changes may cause sound insulation and vibration problems. Although the dynamic performance of traditional floors is well established, the performance of non-traditional shapes is less understood. Before trusting the results of building simulations encompassing optimized floors, the dynamic results should first be validated experimentally. This paper details a numerical finite element analysis method to ascertain the dynamic response of four shaped concrete slabs, with experimental modal analysis used to validate the numerical results. The material properties in the numerical model are updated to match the experimental results. The findings support a computational framework for determining the dynamic response of shaped structures that can then be implemented in future large-scale building models.